Viva o urso sem lenço, sem documento! brincando de ala ursa no carnaval de João Pessoa - Macedo, Lívia Alves dos Santos (2020)
Carnival is a national celebration that involves all Brazilian society, spontaneously or not. There is another structural order in which diverse popular manifestations appear; among them, the Ursa Wing. It is a performance show found notably in Paraíba and Pernambuco (Brazil), which takes place during the carnival and pre-carnival period. The Ursa Wing (or La Ursa) bears the main figure of one or more young people dressed in clothing and mask representing a Bear. Their companions carry a bowl to collect gifts, form a percussion musical group (batucada) and continue walking and dancing through the streets and public spaces, interacting with those they meet along the way. Through a qualitative approach of the ethnographic type, with free interviews, oral reports, audiovisual records and direct and participant observations on the preparation and performance of Ala Ursa Sem Lenço, Sem Document for the carnival of 2019, this research seeks to understand the relationship of the members of this group with the neighborhood of Roger (headquarters of the group) and with the city of João Pessoa. In addition to contributing to understanding the relationship of the groups of Ala Ursas maintain with the city from the Carnival Tradition of João Pessoa, seek to understand the symbols of the SLSD Bears and highlight the organization and production of the 2019 Carnival group. The theoretical references are based on the studies of carnival, ritual and the Ala Ursa manifestation itself, in addition to the city as a festive territory. We realized that the group reinforced markers of ethnicity and social class in its aesthetics and language, and the liveliness of the revelry revealed in the presentations on the beaches, main avenues, streets and squares of the city, strengthens the popular cultural resistance of Roger, neighborhood of origin of the city. group. Thus, Ala Ursa Sem Lenço, Sem Documento also reaffirmed its presence in the city's festive scene, contributing significantly to the socio-educational processes, artistic languages, and selfesteem of its members. It was noticed that the bears (adults and children) of the fun occupy an important space in the local collective imagination, they act as a symbol of cycle renewal associated with the public's fun and fear; being that the Little Bears are more connected to “dancing the Bear” and positive affections of the children of the public, while the Adults to virility and prestige accompanied by responsibility and alcoholic drink. The group is also a powerful political and social instrument in the neighborhood, a space for the construction and re-signification of black individual and group identities; challenging the dominant social structure every year, denying that it is the only form of organization.